99PPatient-derived tumour model by new culture method leading to the precision medicine. (24th November 2019) - Miyoshi, N; Fujino, S; Saso, K; Sasaki, M; Ogino, T; Takahashi, H; Uemura, M; Chu, M; Mizushima, T; Mori, M; Doki, Y
Abstract: Background: Generally, cancer cell lines are established from the patients of which cancer cells are dissected, cultured and maintained in vitro. These cell lines have been traditionally used in cancer research; however, they have changed better to survive in culture condition in vitro, and not restored the original characters when they grew in vivo, meaning the lack of tumor heterogeneity. Primary culture of cancer cells derived from patients' tumors can provide crucial information as each "individual tumor". The primary culture method of clinical cancer and the evaluation for the treatment have not been clearly optimized in gastrointestinal cancers. Methods: We have developed a simple 2D/3D-culture method for primary cancer. We obtained 40 clinical samples from surgically resected colorectal cancers (CRCs). They were mechanically and enzymatically digested and are filtered by customized preparation tools, followed by in vitro culture system. The gene expression profiles and the sensitivity for the drugs were analyzed. Results: Culture cells were analyzed These cultured cancer cells were named "isolated-tumor derived Cancer Cells (iCCs)." All iCCs grew and about 90 % of iCCs were successfully passaged. These iCCs were transplanted into the subcutaneous tissue of nonobese diabetic (NOD) - severely compromised immune deficient (SCID) mice, and the tumor growth and pathological examination were evaluated. The morphology was similar to each parental clinical tumor. Microarray analyses showed that RNA expression of iCCs was similar to each parental tumor. Surface markers regarding cancer stem cells expressed in iCCs. Furthermore, multi-drug sensitivity assay by our bespoke plates including commonly used as anti-cancer/molecular target drugs was performed. Conclusions: The iCCs are very similar to each parental tumor, leading to the personalized medicine, and the analyses of the tumor characteristics seem to reflect the clinical presentation. Legal entity responsible for the study: The authors. Funding: Japanese Agency for Medical Research and Development. Disclosure: All authors have declared no conflicts of interest.